UPAYA PENGENALAN PENTINGNYA MENERAPKAN POLA HIDUP SEHAT DALAM KEHIDUPAN SEHARI-HARI BAGI ANAK SD PIUS BAKTI UTAMA, KEBUMEN - Tjokrosaputro, Miharni; Ariesta, Nicholas; Kennilyn, Thio (Transpublika Publisher, 2023)
A healthy lifestyle is an unavoidable fundamental need for all individuals, although it is often considered a lifestyle that is difficult to implement. This concept is closely related to the lifestyle decisions a person makes in the course of their life. A healthy lifestyle brings a number of very significant benefits, covering both physical and mental health aspects. This research aims to convey understanding to students of SD Pius Bakti Utama, Kebumen, about the urgency of implementing a healthy lifestyle in their daily lives. This community service activity is carried out in the form of online counseling to children of SD Pius Bakti Utama, Kebumen, Central Java, scheduled on November 3, 2023, with an estimated time of about 2 hours. Through this counseling activity, it is expected to instill values and in-depth knowledge related to healthy lifestyles to students, as an investment to increase their awareness of the importance of living a healthy life. This research not only covers the theoretical aspect, but also presents the applicative aspect by providing an online platform that enables effective delivery of materials. Thus, it is hoped that this research can make a positive contribution in shaping healthy mindsets and behaviors, making physical and mental well-being an important aspect of students' daily lives.